Smart solutions in today's transport : 17th International Conference on Transport Systems Telematics, TST 2017, Katowice -- Ustroń, Poland, April 5-8, 2017, Selected papers /: 17th International Conference on Transport Systems Telematics, TST 2017, Katowice -- Ustroń, Poland, April 5-8, 2017, Selected papers. (2017) - Unknown
No abstract available